Aging and Executive Control: Reports of a Demise Greatly Exaggerated - Verhaeghen, Paul (Curr Dir Psychol Sci, 2011)
I report a series of meta-analyses on aging and executive control. A first set of analyses failed to find evidence for specific age-related deficits in tasks of selective attention (inhibition of return, negative priming, flanker, and Stroop) or tasks tapping local task-shifting costs (reading with distractors is an exception) but found evidence for specific age-related deficits in tasks of divided attention (dual tasking and global task-shifting costs). The second set examined whether executive control explained any age-related variance in complex cognition (episodic memory, reasoning, spatial abilities) over and beyond the effects of speed and working memory; it did not. Thus, the purported decline in executive control with advancing age is clearly not general, and it may ultimately play only a small role in explaining age-related deficits in complex cognition.